Genome-wide association study revealed candidate genes associated with egg-laying time traits in layer chicken - Yifan Guo; Yuqi Chen; Huanjie Guo; Binghui Wang; Yiwei Xiong; Jun Ding; Jingyi Li (Poultry Science)
In modern intensive caged laying hen production, variations in egg-laying time (ELT) among layers often increase the workload for egg collection, thereby raising the costs of labor or power and reducing overall efficiency. For management purpose, early and synchronized ELT is also advantageous, particularly to large-scale layer farm. However, the underlying genetic mechanisms of ELT remain unclear. In this study, through the development of video and artificial intelligence-based software, ELT records during the peak laying period (27-32 weeks) from 507 layers, and their earlier laying performance (21-32 weeks) were collected. Via whole genome sequencing data of all the individuals, the estimated heritabilities of traditional egg production traits ranged from 0.23 to 0.36, consistent with previous reports. The heritability of average egg-laying time (AELT) was estimated as 0.46. Furthermore, individuals with earlier AELT tended to exhibit superior egg production performance. Genome-wide association study revealed three SNPs associated with AELT traits, located at 170,867,650 bp on chromosome 1, at 5,548,087 and 5,817,488 bp on chromosome 9. Across the region of 5.4 to 7.0 Mb on chromosome 9, mutations were also identified to be strongly linked with the two AELT-associated SNPs. Genes located in this region may be responsible for the differences in AELT among hens. These results indicate that ELT has the potential to be integrated into the production system of caged layers. If ELT is to be included as a breeding objective in the future, its reliability needs to be validated in larger populations and over longer periods.